Inclusion in Higher Education: Policies and practices at the Federal University of Grande Dourados - Nozu, Washington Cesar Shoiti; Bruno, Marilda Moraes Garcia [UNESP]; Cabral, Leonardo Santos Amâncio (FapUNIFESP (SciELO), 2018)
Considering the implications of the proposal for inclusion in Higher Education, this work aims to investigate the actions of the Federal University of Grande Dourados (UFGD), which have been focused in the last 10 years on the Academic Special Education Target (PAEE). Under the descriptive exploratory case study approach, the research data show policies, organizational practices and strategies, presented and discussed here in three thematic axes: a) Teaching, Research and Extension Actions; b) Services offered to PAEE; c) Inclusion in the UFGD: challenges and perspectives. The results achieved reinforce, in the microcontext investigated, the continuing need for a shared, collective and collaborative responsibility, in order to dislodge the most diverse barriers that are interposed, daily, in the course of university students with specific educational needs.
Inclusão no Ensino Superior: Políticas e práticas na Universidade Federal da Grande Dourados
Keywords: Higher education; Inclusive education; Special education